Gapenski's healthcare finance : an introduction to accounting and financial management - Reiter, Kristin L. (Kristin Leanne); Song, Paula H.; Gapenski, Louis C.; Association of University Programs in Health Administration (Chicago, Illinois : Health Administration Press ; Washington, DC : Association of University Programs in Health Administration, 2021)
"This best-selling textbook covers the essential concepts of accounting and financial management in healthcare"--
Healthcare Finance Basics -- Healthcare Insurance and Reimbursement Methodologies -- Financial Accounting Basics, the Income Statement, and the Statement of Changes in Equity -- The Balance Sheet and Statement of Cash Flows -- Cost Behavior, Organizational Costing, and Profit Analysis -- Departmental Costing and Cost Allocation -- Service Line Costing and Pricing -- Financial Planning and Budgeting -- Time Value Analysis -- Financial Risk and Required Return -- Long-Term Debt Financing -- Equity Financing and Securities Markets -- Capital Structure and the Cost of Capital -- The Basics of Capital Budgeting -- Project Risk Analysis -- Revenue Cycle and Current Accounts Management -- Financial Condition Analysis.
Preceded by Healthcare finance / Louis C. Gapenski, Kristin L. Reiter. Sixth edition. 2016.
Includes bibliographical references and index.
Keywords: Financial Management, Hospital; Health Facilities -- economics; Accounting; Capital Financing